Pengaruh Inventarisasi, Legal Audit, Penilaian dan Kondisi Aset terhadap Optimalisasi Pemanfaatan Aset pada Pemerintah Daerah Kabupaten Bone Bolango - Pauweni, Sherly; Karamoy, Herman; Gamaliel, Hendrik (Universitas Sam Ratulangi, 2017)
Abstract. One of the main problems in the asset management is the asset utilisation and management disorders. This creates difficulties for the local government to identify the assets that they hold or manage, thus the asset utilisation and its management tend not to be optimal. The objective of this research is to analyse the impact of asset management to the optimisation of the asset utilisation at Local Government of Bone Bolango. The variables utilised for this research are stocktaking, legal auditing, assessment and condition of the asset. The samples for this research are 104 people. Respondents were selected through purposive sampling. This is a quantitative research and the method used was multiple regression analysis. The research finding shows that partially, the stocktaking, assessment and condition of the asset have positive and significant impact to the optimisation of asset utilisation; while the legal auditing has no impact toward the optimisation of asset utilisation. The value of the coefficient of determination shows that the stocktaking, legal auditing, assessment and condition of the asset altogether contribute to the optimisation of asset utilisation which is 58,8% and the remaining of 41,2% is affected by the factors beyond this research.Keywords: The Optimization of Asset Utilisation, Stocktaking, Legal Auditing, Assessment, and Condition of the asset.Abstrak. Salah satu masalah utama dalam manajemen aset adalah ketidaktertiban dalam penggunaan dan pemanfaatannya. Ini menyebabkan pemerintah daerah kesulitan untuk mengetahui secara pasti aset yang dikuasai atau dikelolanya, sehingga aset-aset tersebut cenderung tidak optimal dalam penggunaan maupun pemanfaatannya. Penelitian ini bertujuan untuk menganalisis pengaruh manajemen aset terhadap optimalisasi pemanfaatan aset pada Pemerintah Daerah Kabupaten Bone Bolango. Variabel-variabel yang digunakan dalam penelitian ini adalah inventarisasi, legal audit, penilaian dan kondisi aset. Dengan menggunakan purposive sampling, jumlah sampel penelitian yang diambil sebanyak 104 orang. Jenis penelitian ini adalah kuantitatif dengan menggunakan metode analisis regresi berganda. Hasil penelitian menunjukkan bahwa secara parsial inventarisasi, penilaian dan kondisi aset berpengaruh positif dan signifikan terhadap optimalisasi pemanfaatan aset, sedangkan legal audit tidak berpengaruh terhadap optimalisasi pemanfaatan aset. Nilai dari koefesien determinasi menunjukkan bahwa inventarisasi, legal audit, penilain dan kondisi aset bersama-sama berkontribusi terhadap optimalisasi pemanfaatan aset yaitu sebesar 58,8 %, dan sisanya 41,2 % dipengaruhi oleh faktor lain diluar model penelitian.Kata kunci: Optimalisasi Pemanfaatan Aset, Inventarisasi, Legal Audit, Penilaian dan Kondisi AsetÂ